2017
DOI: 10.1007/s13760-017-0811-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after carotid endarterectomy: a review of the literature

Abstract: Strokes are one of the leading causes of death, morbidity, and disability worldwide, mainly among elderly people. It is also the third most common cause of years of life being lost, indicating a high risk of premature mortality. Revascularisation with endarterectomy (CEA) is effective in reducing the risk of death and strokes in patients with carotid artery stenosis, but the effect of invasive treatment on quality of life (QoL) still needs attention. To shed more light on the patients’ perspective on this heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…However, in the BMT group measures of RP, BP and MCS worsened after 6 and 12 months compared to SF-36v2 scores at the beginning of the study. So far, literature review and meta-analysis have shown that CEA and CAS maintain preoperative HRQoL for at least 1 year which is partially congruent with our findings [32, 54]. In our study, most of the patients in the CEA and CAS groups were asymptomatic, whereas symptomatic patients had TIA or minor stroke that was not disabling.…”
Section: Discussionsupporting
confidence: 91%
“…However, in the BMT group measures of RP, BP and MCS worsened after 6 and 12 months compared to SF-36v2 scores at the beginning of the study. So far, literature review and meta-analysis have shown that CEA and CAS maintain preoperative HRQoL for at least 1 year which is partially congruent with our findings [32, 54]. In our study, most of the patients in the CEA and CAS groups were asymptomatic, whereas symptomatic patients had TIA or minor stroke that was not disabling.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous reports. [7,10] The study also found that after 4 weeks of treatment, although the physiological quality of the patients increased significantly, the patient's mental QOL did not show significant improvement. This suggests that in the clinical management of stroke patients, more attention should be paid to improving the psychological conditions of the patients.…”
Section: Discussionmentioning
confidence: 87%
“…Stroke patients face the problems of physical, psychological, social and economic burdens. The patients' health-related quality of life (QOL) was found as low level [3] [4]. Some stroke survivors stated that their QOL would consider as being worse than death after having a stroke [5].…”
Section: Introductionmentioning
confidence: 99%